The Integration of Local Cultural Arts in The Context of Teaching Materials on The Implementation of The Merdeka Belajar Curriculum - Jamilah; Karta Jayadi; Heriyati Yatim; Nurachmy Sahnir; Agussalim Djirong; Amirullah Abduh (Journal of Education Reseach and Evaluation, 2024)
The Merdeka Belajar curriculum emphasizes inclusion and diversity, but there is still a lack of adequate teaching materials that represent various aspects of local culture. Although the Merdeka Belajar Curriculum has provided freedom and flexibility, its implementation still faces several challenges that need to be overcome. One of the main challenges in implementing the Merdeka Belajar Curriculum is the lack of resources. This study aims to analyze the integration of local cultural arts in the context of teaching materials in the implementation of the Merdeka Belajar Curriculum. This type of research is qualitative. The data collection method uses literature study, observation, interviews, FGDs, and document analysis. The data collection instrument used a questionnaire sheet. The participants in this study were teachers and local governments. The data analysis technique used qualitative descriptive analysis. The results showed that the utilization of local cultural arts in teaching materials can strengthen local cultural identity and provide significant and relevant learning experiences for students. Therefore, the Regional Cultural Mindset (PPKD) can be an important guideline in developing teaching materials that are in accordance with regional characteristics and needs and meet the competency standards expected in the Merdeka Belajar Curriculum.